2016
DOI: 10.1002/2015jb012392
|View full text |Cite
|
Sign up to set email alerts
|

Seismic array constraints on the D″ discontinuity beneath Central America

Abstract: We analyzed 16,150 transverse component seismic recordings from 54 deep‐focus earthquakes in the South American and Caribbean regions recorded at broadband stations in North America between 2005 and 2012. We treated subgroups of seismic stations within 3° radius geographical bins as seismic arrays and performed vespagram analysis. We focused on the S, ScS, and Scd arrivals and collected data in the epicentral distance range from 55° to 90°. In particular, we searched for D″ discontinuity presence in the vespag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 67 publications
9
25
0
Order By: Relevance
“…Our observations appear to support the notion that subducting slabs, at least in part, more likely accumulate eventually at the base of the mantle (e.g., Hutko et al, ). Our detection of pv‐ppv transition is also consistent with the majority of observations that the D" discontinuity is often seen at regions with a velocity faster than average lower mantle seismic wave speeds; for example, the discontinuity is observable beneath Alaska (e.g., Sun et al, ) and Central America (e.g., Whittaker et al, ), whereas the occurrence of the discontinuity beneath slow regions in D" is primarily confined to the central Pacific region (e.g., Avants et al, ). It has been suggested that slow region D" discontinuities may have an origin distinct from those in fast regions (Hernlund & McNamara, ).…”
Section: Discussionsupporting
confidence: 89%
“…Our observations appear to support the notion that subducting slabs, at least in part, more likely accumulate eventually at the base of the mantle (e.g., Hutko et al, ). Our detection of pv‐ppv transition is also consistent with the majority of observations that the D" discontinuity is often seen at regions with a velocity faster than average lower mantle seismic wave speeds; for example, the discontinuity is observable beneath Alaska (e.g., Sun et al, ) and Central America (e.g., Whittaker et al, ), whereas the occurrence of the discontinuity beneath slow regions in D" is primarily confined to the central Pacific region (e.g., Avants et al, ). It has been suggested that slow region D" discontinuities may have an origin distinct from those in fast regions (Hernlund & McNamara, ).…”
Section: Discussionsupporting
confidence: 89%
“…The D″ layer beneath the Antarctic Ocean and New Zealand is approximately~350 km thick based on waveform modeling and traveltime analysis [Usui et al, 2005]. The global average D″ thickness is approximately 250 to 300 km, based on studies of various regions including Alaska [Sun et al, 2016], southeastern Asia [Chaloner et al, 2009], Russia [Shen et al, 2014], Central America [Lay and Helmberger, 1983;Whittaker et al, 2015], and the Indian Ocean [Young and Lay, 1987]. Usui et al [2005] attribute the thicker than average D″ beneath our study region due to the presence of paleo-slab material, in agreement with the inferences of Steinberger [2000b].…”
Section: Introductionmentioning
confidence: 99%
“…Both an ULVZ [Havens and Revenaugh, 2001] or a strong discontinuity in D'' [Lay et al, 2004;Lay, 2008;Sun et al, 2006;Kito et al, 2007;Whittaker et al, 2015] could affect our measurements. Considering the long period of the ScS waveforms used in this study (i.e., on the order of 700 km), there are two documented structures in the lower mantle beneath Mexico that are likely to have lateral variations on a small scale.…”
Section: Lateral Heterogeneities: the Cocos Slab And The Lower Mantlementioning
confidence: 95%
“…Under the Cocos Plate, several studies suggest that the sharpness of the D'' discontinuity and its topography have notable influence on phase arrivals [Lay et al, 2004;Lay, 2008;Sun et al, 2006;Kito et al, 2007;Whittaker et al, 2015]. Under the Cocos Plate, several studies suggest that the sharpness of the D'' discontinuity and its topography have notable influence on phase arrivals [Lay et al, 2004;Lay, 2008;Sun et al, 2006;Kito et al, 2007;Whittaker et al, 2015].…”
Section: Focusing On Small Aperturementioning
confidence: 99%
See 1 more Smart Citation